Mortalitas Larva Litopenaeus vannamei Pada Penerapan Perbedaan Sistem Filtrasi Air Media Pemeliharaan - Sunaryo Sunaryo; I Nyoman Widiasa; Ali Djunaedi; Priyo Sasmoko (Universitas Diponegoro, 2018)
Mortality of Litopenaeus vannamei larvae with the different filtration system of seawater as media for rearingMortality of Litopenaeus vannamei larvae in shrimp hatcheries centers is commonly high. Therefore, innovation to solve the problem through water quality management improvement in necessary by applying ultrafiltration system to shrimp hatchery. This experiment aims to determine larval mortality rate in response to the application of different filtration systems. Experiments were conducted using 4 milions larvae of L. vannamei shrimp. Shrimp larvae were kept in 4 tanks, each volume was 8 m3. Two reservoirs tank were equipped with ultrafiltration and other systems used sand-filter as controls. Implementation of experimental activities used action research method with two repetitions. Observation were conducted on mortality of shrimp larvae and water quality, i.e., temperature, salinity, pH, TSS, dissolved O2, NH3 and NO3-2. The result showed the shrimp larvae reared with the application of ultrafiltration system had significantly lower percentage of mortality (55,02 %) compared with filtering using sand-filter (59,58 %). Concentrations of Ammonia (NH3-N) and TSS content increased along with longer period of larval rearing.Mortalitas larva udang Litopenaeus vannamei di sentra pembenihan masih tinggi. Inovasi sistem pengendalian kualitas air pada media pembenihan udang perlu dilakukan. Percobaan dilakukan untuk mengetahui respon tingkat mortalitas larva Litopenaeus vannamei denan penerapan perbedaan sistim filtrasi. Pelaksanaan percobaan menggunakan metode action research dengan pengulangan 2 kali. Percobaan dilakukan dengan menggunakan larva Udang Litopenaeus vannamei stadia larva sebanyak 4 juta ekor. Larva Udang dipelihara dalam 4 buah bak. Dua buah bak dilengkapi dengan sistem ultrafiltrasi dan bak lainnya menggunakan sandfilter sebagai kontrol. Pengamatan dilakukan terhadap mortalitas larva udang, suhu, salinitas, pH, MPT, O2 terlarut, NH3 dan NO3-2. Hasil penelitian menunjukkan bahwa rata-rata mortalitas Larva udang Vannamei yang dipelihara dengan pola pemeliharaan dengan penerapan sistim ultrafiltrasi adalah 55.02% yang berbeda sangat nyata (p>0,01) dibandingkan dengan penerapan pola pemeliharaan menggunakan sandfilter yaitu 59,58% . Kualitas air media pemeliharaan larva udang Vannamei, terutama: kandungan Ammoniak (NH3-N) dan MPT menunjukkan semakin meningkat dengan semakin lamanya waktu pemeliharaan.